2022
DOI: 10.1002/nop2.1317
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of unplanned endotracheal extubation in intensive care unit: An overview of systematic reviews

Abstract: Aims This study was performed to identify and summarize systematic reviews focusing on the prevention of unplanned endotracheal extubation in the intensive care unit. Design Overview of systematic reviews. Methods This overview was conducted according to the Preferred Reporting Items for Overviews of Systematic Reviews, including the harms checklist. A literature search of PubMed, the Cochrane Library, CINAH, Embase, Web of Science, SINOMED and PROSPERO was performed from January 1, 2005–June 1, 2021. A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…However, securing the ETT with a suitable fixation system to prevent unplanned extubation is a matter that needs to be addressed. In their recent review, Wu and al [15] recommend carrying out more randomized controlled trials related to ETT fixation. The present study could provide data to make progress on that topic An independent safety committee (ISC) board has been constituted after the start of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, securing the ETT with a suitable fixation system to prevent unplanned extubation is a matter that needs to be addressed. In their recent review, Wu and al [15] recommend carrying out more randomized controlled trials related to ETT fixation. The present study could provide data to make progress on that topic An independent safety committee (ISC) board has been constituted after the start of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, fixation systems developed by the pharmaceutical industry exert more pressure on the facial skin as suggested by a mannequin study comparing 10 sophisticated industrial systems and 6 "simple" systems [ 10 ]. Regarding preventive measures for the prevention of unplanned endotracheal extubation in the ICU, a recent review concluded that an optimal method of endotracheal tube fixation has not been established [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature search for risk factors, preventive strategies, and KAP, 13–24 as well as the theoretical framework of KAP, 25,26 a total of 91 initial items were prepared as a part of the primary questionnaire. In the knowledge section, there was only one correct answer for each item, and each correct answer was given 1 point.…”
Section: Methodsmentioning
confidence: 99%
“…Based on literature search for risk factors, preventive strategies, and KAP, [13][14][15][16][17][18][19][20][21][22][23][24] as well as the theoretical framework of KAP, 25,26 a total of 91 initial items were prepared as a part of the primary questionnaire.…”
Section: Preparation For the Primary Questionnairementioning
confidence: 99%
See 1 more Smart Citation